2015
DOI: 10.1371/journal.pone.0139610
|View full text |Cite
|
Sign up to set email alerts
|

Fingerspelling as a Novel Gateway into Reading Fluency in Deaf Bilinguals

Abstract: Studies have shown that American Sign Language (ASL) fluency has a positive impact on deaf individuals’ English reading, but the cognitive and cross-linguistic mechanisms permitting the mapping of a visual-manual language onto a sound-based language have yet to be elucidated. Fingerspelling, which represents English orthography with 26 distinct hand configurations, is an integral part of ASL and has been suggested to provide deaf bilinguals with important cross-linguistic links between sign language and orthog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 37 publications
1
42
0
2
Order By: Relevance
“…Imitation of lexical manual gestures may reveal the ability of sign language users to manipulate representations from the lexical system, and may thus involve processes of importance for reading development. Prior to the present work, however, no one had investigated how the ability to imitate different types of lexical manual gestures relates to developing reading in DHH signing children, although imitation of sign language has been connected to reading skills in earlier studies of deaf adults (e.g., Freel, Clark, Anderson, Gilbert, Musyoka, & Hauser, 2011;Stone, Kartheiser, Hauser, Petitto, & Allen, 2015).…”
Section: Efficient Language Processing and Imitationmentioning
confidence: 99%
See 4 more Smart Citations
“…Imitation of lexical manual gestures may reveal the ability of sign language users to manipulate representations from the lexical system, and may thus involve processes of importance for reading development. Prior to the present work, however, no one had investigated how the ability to imitate different types of lexical manual gestures relates to developing reading in DHH signing children, although imitation of sign language has been connected to reading skills in earlier studies of deaf adults (e.g., Freel, Clark, Anderson, Gilbert, Musyoka, & Hauser, 2011;Stone, Kartheiser, Hauser, Petitto, & Allen, 2015).…”
Section: Efficient Language Processing and Imitationmentioning
confidence: 99%
“…Using these symbols to represent a written word in the manual modality is referred to as fingerspelling (Morere & Roberts, 2012). It has been suggested that fingerspelling can actually provide sign language users with a phonological code of written words in the manual modality that they can use as a bridge across language modalities (Crume, 2013;Haptonstall-Nykaza & Schick, 2007), and there is some empirical support for this (Hanson, Liberman, & Shankweiler, 1984;Haptonstall-Nykaza & Schick, 2007;Stone et al, 2015). In particular, it has been suggested that fingerspelling may support the development of precise and rapid word identification (Stone et al, 2015).…”
Section: Sign Language Skills and Learning To Read Wordsmentioning
confidence: 99%
See 3 more Smart Citations